PENGEMBANGAN SUMBER DAYA MANUSIA DALAM TRANSFORMASI DIGITAL DI ERA INDUSTRI 4.0 - Andhika Putra, Rio; Bayu Putra, Ramdani; Fitri, Hasmaynelis (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2022)
Currently, educational institutions are the main forum in preparing reliable and competent human resources (HR) to support the implementation of development and progress of the nation in the future. One of the educational institutions based on Islamic education is the Rahmatan Lil 'Alamin International Islamic Boarding School in Aripan, Solok Regency. This educational institution does not only teach education related to the Islamic religion but also teaches and educates complete scholarship, whether it is related to language, technology or soft skills or skills in various fields. Since its establishment in 2020, it has had complete and adequate facilities and infrastructure with beautiful surroundings and views with panoramic views of the hills and lakes of Singkarak below. The purpose of this Community Service activity is that students or students are expected to be able to gain broad knowledge and understanding in the latest technological developments and advances and their benefits in supporting work activities and people's daily lives. And through this activity, students are also expected to have scientific interests and talents to determine the direction of education and expertise they are interested in in the future.